2012
DOI: 10.1103/physrevlett.108.015503
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Velocity Dependence of Adhesion in a Nanometer-Sized Contact

Abstract: The influence of sliding velocity on the adhesion force in a nanometer-sized contact was investigated with a novel atomic force microscope experimental setup that allows measuring adhesion forces while the probe is sliding at continuous and constant velocities. For hydrophobic surfaces, the adhesion forces (mainly van der Waals forces) remain constant, whereas for hydrophilic surfaces, adhesion forces (mainly capillary forces) decrease linearly with a logarithmic increase of the sliding velocity. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…Although AFM tip in our experiments constantly moves relative to Au NPs, the velocities of the tip are not high enough to completely exclude the formation of capillary bridges between the tip and particle [37]. The AFM force-curves are conducted at a rate of 2 kHz allowing a contact of both surfaces in the order of the milliseconds [3839] at ambient temperature (20 °C) and relative humidity around 35 ± 5%.…”
Section: Resultsmentioning
confidence: 99%
“…Although AFM tip in our experiments constantly moves relative to Au NPs, the velocities of the tip are not high enough to completely exclude the formation of capillary bridges between the tip and particle [37]. The AFM force-curves are conducted at a rate of 2 kHz allowing a contact of both surfaces in the order of the milliseconds [3839] at ambient temperature (20 °C) and relative humidity around 35 ± 5%.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we focus on F cap as a function of h. As many experiments indicate, capillary forces also contribute significantly to sliding friction and lead to unusual velocity dependence (dynamics) and time dependence (kinetics) [15][16][17][18][19]. It would be interesting to extend the current study to the cases where the tip is displaced laterally so that the liquid bridge is dragged over the substrate surface.…”
Section: Discussionmentioning
confidence: 97%
“…For example, they often prevent micro-or nanoelectromechanical systems from functioning under ambient conditions or lead to damage in their fabrication processes [14]. They play a major role in nanoscopic sliding friction and lead to a nontrivial velocity dependence of friction [15][16][17][18][19]. Many previous experiments also show that when an atomic force microscope (AFM), or more generally any small probe, is used to examine a hydrophilic surface in a humid environment, a major contribution to the tipsurface interaction is from the capillary forces associated with the water meniscus bridging the tip and surface [15,[20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…We found that a better transfer result can be achieved by peeling off the filter with a quick movement, which is contradictory to the traditional transfer printing processes28. This could be related to the redistribution of water capillary force2930 due to the hydrophilic and porous nature of the PVDF filter, which differs itself from an elastic smooth surface such as PDMS typically used in other transfer printing processes. Afterwards, the gel cake/acrylic structure is soaked in IPA for solvent exchange, and the gel cake can be separated from the acrylic with a little shake.…”
Section: Methodsmentioning
confidence: 82%